Genetic parameters of production efficiency traits in Tharparkar cattle - S.S Dhakal; S.R. Chaudhary; B.L. Pander; S. Singh (Journal of Livestock Biodiversity, 2025)
The data on 303 Tharparkar cows, progeny of 13 sires calved during 1974 to 1993 maintained at Government Livestock Farm, Hisar were considered for the estimation of genetic parameters. The means for first lactation milk yield (FLY), wet average (WA), first lactation peak yield (FPY), first lactation milk yield per day of first calving interval (MCI) and first lactation milk yield per day of age at second calving (MSC) were 1300.73 Kg. 483 Kg day, 7.49 Kg/day, 2.74 Kg/day and 0.682 Kg/day, respectively. The effect of period of calving was significant (P<0.05) on FLY and MSC while the effect of season of calving was significant on all the production efficiency traits. Monsoon calvers excelled in performance for all the production efficiency traits. The effect of age at first calving (linear) was significant only on MSC. Estimates of heritability for all the traits were low and ranged from 0.117 to 0.143 except for WA (0.273). All the genetic and phenotypic correlations among different production efficiency traits were high and positive. It may be inferred that selection on the basis of wet average will be more effective as the trait is expressed early in life and had reasonably moderate estimate of heritability.